Assessment of selected physico-chemical parameters of the Buriganga river, Bangladesh (Bangladesh Journal of Zoology, 2026)
A study was conducted on the physico-chemical parameters in the Buriganga River at Wise Ghat and Postogola Bridge, Dhaka, Bangladesh, on a monthly basis from October 2023 to September 2024. The purpose of this study is to evaluate the present water quality status based on six selected physico-chemical properties of water including water temperature, transparency, total dissolved solids (TDS), electrical conductivity (EC), pH and dissolved oxygen (DO). Minimum average temperature was observed 19.4 °C in January while maximum average temperature was 33.6 °C in November. The Minimum and the maximum value of average transparency of the river water was determined as 21.8 cm in May and 52.6 cm in October, respectively. Minimum average TDS was 85 ppm in July and maximum average TDS was 403 ppm in May. Minimum average EC was 150 µS/cm in October and maximum average was 589.5 µS/cm in May.  pH of the water found more stable round the year which ranged from 7.4 to 7.8 and annual mean pH value was 7.62. DO of the water showed a greater fluctuation, which ranged from 0.9 ppm in May to 7.25 ppm in September. Some parameters were not within the standard limit for aquatic life. A regular monitoring system could be developed to prevent further deterioration of water condition and restoration of the ecosystem of the Buriganga River.Bangladesh J. Zool. 53(3): 285-296, 2025